Prony Analysis for Power System Transient Harmonics. (7th February 2007) - Qi Qi, Li Li; Qian Qian, Lewei Lewei; Woodruff Woodruff, Stephen Stephen; Cartes Cartes, David David
Abstract : Proliferation of nonlinear loads in power systems has increased harmonic pollution and deteriorated power quality. Not required to have prior knowledge of existing harmonics, Prony analysis detects frequencies, magnitudes, phases, and especially damping factors of exponential decaying or growing transient harmonics. In this paper, Prony analysis is implemented to supervise power system transient harmonics, or time-varying harmonics. Further, to improve power quality when transient harmonics appear, the dominant harmonics identified from Prony analysis are used as the harmonic reference for harmonic selective active filters. Simulation results of two test systems during transformer energizing and induction motor starting confirm the effectiveness of the Prony analysis in supervising and canceling power system transient harmonics.